2015
DOI: 10.3748/wjg.v21.i43.12234
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan, a key chemotherapeutic drug for metastatic colorectal cancer

Abstract: Irinotecan hydrochloride is a camptothecin derivative that exerts antitumor activity against a variety of tumors. SN-38 produced in the body by carboxylesterase is the active metabolite of irinotecan. After irinotecan was introduced for the treatment of metastatic colorectal cancer (CRC) at the end of the last century, survival has improved dramatically. Irinotecan is now combined with 5-fluorouracil, oxaliplatin and several molecularly-targeted anticancer drugs, resulting in the extension of overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
172
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(173 citation statements)
references
References 103 publications
1
172
0
Order By: Relevance
“…Interestingly, cimetidine is a well-characterized inhibitor of OCT2 (36). Irinotecan usually co-administration with morphine in advanced colorectal cancer (12,44). Our present study demonstrated that irinotecan had the most potent inhibitory effect among these tested drugs on the uptake of morphine mediated by the hepatic OCT1 and by the renal OCT2.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cimetidine is a well-characterized inhibitor of OCT2 (36). Irinotecan usually co-administration with morphine in advanced colorectal cancer (12,44). Our present study demonstrated that irinotecan had the most potent inhibitory effect among these tested drugs on the uptake of morphine mediated by the hepatic OCT1 and by the renal OCT2.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, irinotecan is key chemotherapeutic drug for metastatic colorectal cancer and other types of tumors. 33 Topotecan is used to treat cancer of the ovaries when other treatments have failed and may also be used in certain types of lung cancer (small cell lung cancer). Since Tdp1 is involved in the removal of DNA damage caused by CPT, it is believed that Tdp1 is responsible for drug resistance of some cancers.…”
Section: Synergistic Activity With Camptothecin Against Tumor Cellsmentioning
confidence: 99%
“…Future research on the protective activities of the metabolic products of resveratrol are necessary to elucidate their interaction with DNA-damaging drugs used in the treatment of cancer. Of note, camptothecins are used in the combinatorial treatment of colorectal cancers (46)(47)(48). The increased DNA damage and apoptosis of cells treated with camptothecin and topotecan following pretreatment with resveratrol aglycone in the present study suggests that dietary resveratrol may be a useful addition for treating gastrointestinal cancers that have direct contact with unmetabolized resveratrol.…”
Section: Discussionmentioning
confidence: 63%